The honeysuckle genome provides insight into the molecular mechanism of carotenoid metabolism underlying dynamic flower coloration. Issue 3 (18th April 2020) - Pu, Xiangdong; Li, Zhen; Tian, Ya; Gao, Ranran; Hao, Lijun; Hu, Yating; He, Chunnian; Sun, Wei; Xu, Meimei; Peters, Reuben J.; Van de Peer, Yves; Xu, Zhichao; et al.
Summary: Lonicera japonica is a widespread member of the Caprifoliaceae (honeysuckle) family utilized in traditional medical practices. This twining vine honeysuckle also is a much‐sought ornamental, in part due to its dynamic flower coloration, which changes from white to gold during development. The molecular mechanism underlying dynamic flower coloration in L. japonica was elucidated by integrating whole genome sequencing, transcriptomic analysis and biochemical assays. Here, we report a chromosome‐level genome assembly of L. japonica, comprising nine pseudochromosomes with a total size of 843.2 Mb. We also provide evidence for a whole‐genome duplication event in the lineage leading to L. japonica, which occurred after its divergence from Dipsacales and Asterales. Moreover, gene expression analysis not only revealed correlated expression of the relevant biosynthetic genes with carotenoid accumulation, but also suggested a role for carotenoid degradation in L. japonica's dynamic flower coloration. The variation of flower color is consistent with not only the observed carotenoid accumulation pattern, but also with the release of volatile apocarotenoids that presumably serve as pollinator attractants. Beyond novel insights into the evolution and dynamics of flower coloration, the high‐quality L. japonica genome sequence also provides a foundation for molecular breeding to improve desired characteristics.